Neonatal Cholestasis Over Time: Changes in Epidemiology and Outcome in a Cohort of 154 Patients From a Portuguese Tertiary Center - Santos Silva, Ermelinda; Almeida, Alexandra; Frutuoso, Simão; Martins, Esmeralda; Valente, Maria João; Santos-Silva, Alice; Lopes, Ana Isabel (Frontiers in Pediatrics, 2020)
management of neonatal cholestasis, which may have changed its epidemiology, diagnostic accuracy, outcomes and survival. Our goal was to characterize these changes over time in our setting. Methods: Retrospective cohort study in a tertiary center, enrolling patients born between January 1985 and October 2019. The cohort was divided into two periods, before (A; n=67) and after (B; n=87) the year 2000; and in two groups, according to patient´s outcome (favourable, unfavourable). Overall survival and survival without orthotopic liver transplant (OLT) were evaluated in the two periods (A and B) and in different subgroups of underlying entities. Results: We found that the age of cholestasis recognition decreased significantly from period A to period B [median 43 days and 22 days, respectively, p<0.001)]; the changes in epidemiology were relevant, with a significant decrease in alpha-1-antitrypsin deficiency (p<0.001) and an increase in transient cholestasis (p=0.004). A next-generation sequencing (NGS) panel available since mid-2017 was applied to 13 patients with contributory results in 7, but, so far, only in 2 patients led to conclusive diagnosis of underlying entities. The number of cases of idiopathic cholestasis did not vary significantly. Over time there was no significant change in the outcome (p=0.116). Overall survival and survival without OLT had no significant improvement during the period of observation (in periods A and B, 86% versus 88%, and 85% versus 87%, respectively). However, in period B, with OLT we achieved the goal of 100% of survival rate. Conclusions: Our data suggest that transient cholestasis became a very important subset of neonatal cholestasis, requiring specific guidance. The NGS panels can provide important inputs on disease diagnosis but, if applied without strict criteria and expertise, they can open a Pandora's box due to misinterpretation. Despite all the advances in accurate diagnosis and timely management – including early recognition of cholestasis - the improvement in patient outcomes and survival were still not significant.